Efektifitas Sistem Informasi Pembelajaran dengan Media E-Learning di MAN 1 Pangandaran - Tatin Suhertin; Indri Ramdani; Putri Ribcha Azzahra; Irwan Nurjamiludin; Devi Silvia Dewi (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
The Covid-19 pandemic has had a major impact in various ways, especially in the field of education, teaching and learning activities cannot be carried out directly, face to face between teachers and students. Online learning allows teaching materials to be delivered to students via the internet without having to meet in person. The aim of this research is to obtain an overview of the effectiveness of using E-learning based learning media at MAN 1 Pangandaran. The subjects of this research are teachers who are responsible for managing E-learning at MAN 1 Pangandaran. This research uses a qualitative research approach with a case study method. The data collection techniques used were interviews, observation and documentation studies. The results of this research show that learning using the e-learning system at MAN 1 Pangandaran was effective during the Covid-19 pandemic, but because the Covid-19 pandemic has improved, the e-learning system is only used for exams.